Peran Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Pendidikan - Sulkifli; Ahmad Rifai; Sri Mulya Maharani A; Dian Chaerani; Nurhaliza Ramly (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
Improving the quality of education is a major challenge in the implementation of education in Indonesia. One of the strategic factors that supports the achievement of educational quality is effective management of facilities and infrastructure. This study aims to thoroughly examine the definition of facilities and infrastructure management, quality management in education, as well as the concept of Total Quality Management (TQM) and its implementation in the educational context. The method used is a qualitative descriptive approach through literature study. The results of the review indicate that facilities and infrastructure management based on TQM principles can have a positive impact on the teaching and learning process and the achievement of educational goals. Synergy among stakeholders is needed to ensure the success of facilities and infrastructure management in continuously improving the quality of education.